Economic evaluation and budgetary burden of mepolizumab in severe refractory eosinophilic asthma - Manuel David Gil-Sierra; Leticia García-Mochón; Emilio Jesús Alegre-del Rey; Catalina Alarcón de la Lastra-Romero; Marina Sánchez-Hidalgo (Farmacia Hospitalaria)
Objective: Mepolizumab is indicated as an additional treatment of severe refractory eosinophilic asthma. The observed differences in population subgroups according to plasma eosinophil count, the existence of patients with high levels of immunoglobulin E who are candidates of omalizumab and mepolizumab, as well as mepolizumab’s economic impact, lead to make efficient economic studies for clinical decision making. The aim was to analyze mepolizumab’s cost-efficacy and budget impact. Method: Cost comparison and the use of mepolizumab’s budgetary impact was performed, from the Spanish National Health System’s perspective. Among the assessed alternatives, inhaled systemic corticosteroids, plus long acting beta agonist (β2) and/or oral systemic corticosteroids in patients with non immunoglobulin E-mediated severe allergic asthma, and said treatment along with omalizumab in patients with immunoglobulin E mediated eosinophilic allergic asthma were included. Its efficacy was evaluated through avoided clinically relevant exacerbations. The direct costs associated with exacerbation were assessed. Results: Mepolizumab’s long run average incremental cost regarding omalizumab’s is 797 euros per patient a year. Considering omalizumab’s alternative discounted price, including mepolizumab for patients with immunoglobulin E mediated eosinophilic allergic asthma would increase public spending from 2.3 to 4.6 million euros. Given omalizumab’s notified price, the gradual introduction of mepolizumab in the Spanish National Health System would save 3.6 million euros in three years. For non immunoglobulin E-mediated severe asthma patients, the avoided cost/exacerbation by introducing mepolizumab is 15,085 euros, assuming a gradual market penetration of mepolizumab. In patients with ≥ 500 eosinophils/μL, this cost decreases to 7,767 euros per avoided exacerbation with a budgetary impact of 183.2 million euros in three years with a progressive penetration of mepolizumab. Conclusions: The cost comparison between mepolizumab and omalizumab in immunoglobulin E mediated eosinophilic asthma patients suggests a use of the lower cost drug, promoting price competition. Additionally, prioritizing its use among non immunoglobulin E-mediated severe refractory eosinophilic asthma patients and ≥ 500 eosinophils/μL plasma level patients, would improve its efficiency as well as reducing its budgetary impact.